PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN APLIKASI PREZI UNTUK MENINGKATKAN LITERASI MATEMATIS SISWA KELAS XI SMA SWASTA TELADAN MEDAN - Srg, Putri Seika; Syahlan, Syahlan; Octariani, Dhia (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
This study aims to produce learning media assisted by the Prezi application on arithmetic sequences and series at SMA Swasta Teladan Medan based on valid, practical and effective criteria and can see the increase in students' mathematical literacy skills after using the developed learning media. The learning device development model used is by referring to the Thiagarajan model which consists of four stages, namely: 1) Define stage, 2) Design / design stage, 3) Development / development stage and, (4) Disseminate / Deployment. The results of the research on the development of learning media assisted by the Prezi application on arithmetic sequences and series at the Medan Teladan Private High School meet the valid criteria in the media, material and language aspects, an average score of 3.93 and is in the good category, practical in terms of convenience, attractiveness, helpfulness and problem solving with an average score of 90.33% is in the Very Practical category, and is effectively obtained through student learning outcomes tests with an average score of 85% and in the good category.Keywords: Prezi, mathematical literacy, 3-D